ANALISIS INFORMASI MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN CONSUMER GOODS INDUSTRY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Duma Rahel Situmorang; Lidia Anggita Purba (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2021)
The purpose of this study is to analyze the impact of intellectual capital information on firm value. This study focused on the descriptive qualitative methods. The firm value in this study is measured using Tobin’s Q. While the intellectual capital is measured using the Value Added Intellectual Coefficient (VAICTM). The population in this study is all the companies in the Consumer Goods Industry are included in 50 Biggest Market Capitalization were listed on the Indonesia Stock Exchange from 2013 to 2017. The result showed that the application of the information of intellectual capital on the company in the Consumer Goods Industry has a level of efficiency of intellectual capital that is great in creating added value and increase competitive advantage.Increased competitive advantage and value, then the perception of the market on the value of the firm will be increased because it is believed that the companies have a competitive advantage are able to compete and survive in a dynamic business environment. This was confirmed by the value Tobin's Q > 1 indicating that management was successful in managing the assets of the company and has a high investment growth potential.